Προσομοίωση δικτυωμένων ρομποτικών συστημάτων με δυνατότητα πειραματικής υλοποίησης - Κακουλλής, Γιώργος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
In the last decade, the attention of planning and cooperative control of robotic systems has grown enormously in the control community. As a result, a rapid development took place in the field of robotics.Various kinds of robots have been invented to date, the majority of them, used in research.The goal of the present thesis, is the simulation, with the possibility of experimental realization, of the control of a non-holonomic unicycle robot.The robotic platform which has been under investigation is turtlebot.So,the kinematic and dynamic model was developed in the presence of kinematic constrains.A closed - loop speed controller was then applied, which focuses on the parking problem in the absence of obstacles.The controller ensures the stability of the system, since it is developed through the direct method of Lyapunov.A camera was simulated and used as a sensor for the system.The simulation includes, induction of noise terms in the sensor measurements, and filtering through filter.For the signal - filter process, a Kalman filter for non¬linear systems was applied, namely Unscented Kalman Filter. Therefore, codes were developed in C and C++ programming languages, through which the filtering process was examined in conjunction with the control problem.The final simulation of the system was held in the Gazebo, which is perhaps the best simulator that exists today in the field of robotics.To achieve this, an extensive study and use, of the robotic operating system - ROS and the operating system Linux, was necessary.The successful simulation of the system in the Gazebo simulator guarantees the possibility of experimental realization without any code change.
Keywords: Robotic systems; Ρομποτικά συστήματα